FORMULASI SEDIAAN SABUN CAIR KOMBINASI EKSTRAK ETANOL DAUN KERSEN (Muntingia calabura L.) DAN DAUN KEMANGI (Ocymum basilicum L.) DAN UJI TERHADAP BAKTERI Staphylococcus aureus - Nau'e, Dwi A.K.; Yamlean, Paulina V. Y.; Mpila, Deby A. (UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTKersen leaves (Muntingia Calabura L.) and Basil leaves (Ocymum basilicum L.) are plants that contain flavonoid compounds, saponin and tannin which acts as antibacterial. The aims of this study is formulate liquid soap in combination of ethanol extract of Kersen leaves and basil leaves and to test the antibacterial effectiveness and evaluate the physical preparates of liquid soap in combination of ethanol extract of Kersen leaves and Kemangi leaves. This research uses a laboratorium experimental method. Based on the results of the study showed physical evaluations such as organoleptics which are dark green and dark brown, Soap pH above 8, measurement height of foam 60-88 mm, calculation of water content was 46%, free alkali content was 0,05-0,06 g/ml, and specific gravity was 1,01-1,09 g/ml. Liquid soap combination of Kersen and Basil leaves extract has antibacterial effectiveness of average diameter for FI 10 mm, F2 10,33 mm, F3 11 mm, F4 11,5 mm, and F5 10,67 mm. In conclusion, the combination of Kersen and Basil leaves extract can be formulated into liquid soap, liquid soap preparations in physical evaluation testing had met the standards set by SNI. Liquid soap preparation has antibacterial effectiveness which is included in the strong category.Keywords: Antibacterial, Liquid Soap, Kersen, Basil.ABSTRAK Daun Kersen (Muntingia Calabura L.) dan Daun Kemangi (Ocymum basilicum L.) merupakan tanaman yang memiliki kandungan senyawa flavonoid, saponin dan tannin yang bersifat sebagai antibakteri. Penelitian ini bertujuan untuk memformulasikan sabun cair kombinasi ekstrak etanol daun Kersen dan daun Kemangi serta menguji efektivitas antibakteri dan mengevaluasi sediaan fisik dari sabun cair kombinasi ekstrak etanol daun Kersen dan daun Kemangi. Penelitian ini menggunakan metode ekperimental laboratorium. Berdasarkan hasil penelitian menunjukkan evaluasi fisik seperti organoleptik berwarna hijau tua dan cokelat tua, pH sabun diatas 8, pengukuran tinggi busa 60-88 mm, perhitungan kadar air yaitu 46%, kadar alkali bebas yaitu 0,05-0,06 g/ml, dan bobot jenis yaitu 1,01-1,09 g/ml. Sediaan sabun cair kombinasi ekstrak daun Kersen dan daun Kemangi memiliki efektifitas antibakteri diameter rata-rata untuk FI 10 mm, F2 10,33 mm, F3 11 mm, F4 11,5 mm, dan F5 10,67 mm. Kesimpulannya kombinasi ekstrak daun Kersen dan daun Kemangi dapat diformulasikan menjadi sabun cair, sediaan sabun cair dalam pengujian evaluasi fisik telah memenuhi standar yang ditetapkan oleh SNI. Sediaan sabun cair memiliki efektifitas antibakteri yang termasuk kategori kuat.Â Kata Kunci: Antibakteri, Sabun Cair, Kersen, Kemangi.